2021
DOI: 10.3991/ijet.v16i10.20795
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Changing Education System at Universities in The Pandemic Process Based on The Opinions of Faculty Members and Students

Abstract: Covid-19, which emerged in the Wuhan city of People’s Republic of China and affected the whole world, was first seen in Turkish Republic of Northern Cyprus and Turkey in March 2020. Due to the negative impact created by the mentioned disease, face-to-face education which was traditionally applied in Turkey and Northern Cyprus was ceded and total distance education was adopted rapidly so that education would not be hindered. Although distance education has a long history in the world, the total transformation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Kormaz et al [9] listed the advantages of distance education to educators and students, which include saving time, flexible teaching and learning pedagogies with educational tools available online, and flexible teaching and learning time. Despite the advantages of open and distance learning, educators and students are also facing difficulties in adapting and adopting teaching and learning changes, such as stability of internet connection, digital literacy, and familiarity with tools or technical aspects of teleconferencing or online teaching application [3], [14].…”
Section: Preferred Teaching and Learning Approach During The Covid-19...mentioning
confidence: 99%
See 1 more Smart Citation
“…Kormaz et al [9] listed the advantages of distance education to educators and students, which include saving time, flexible teaching and learning pedagogies with educational tools available online, and flexible teaching and learning time. Despite the advantages of open and distance learning, educators and students are also facing difficulties in adapting and adopting teaching and learning changes, such as stability of internet connection, digital literacy, and familiarity with tools or technical aspects of teleconferencing or online teaching application [3], [14].…”
Section: Preferred Teaching and Learning Approach During The Covid-19...mentioning
confidence: 99%
“…Thus, the challenges and impacts of teaching and learning during the COVID-19 pandemic focus on the implementation of open and distance learning as a flexible learning pathway where content must be made available in a way that students can access it anytime and anywhere, as reported by Müller et al [8], Kormaz et al [9], Yaseen et al [10]. Müller et al [8], Kormaz et al [9], and Yaseen et al [10] stated that with flexible learning through open and distance learning, students have access to at least one of the following dimensions: time, place, pace, learning style, content, assessment, or learning pathway, which can be assessed online and offline (recorded lectures). In addition to these factors, it is also important to consider educator/learner facilities and equipment, digital literacy, and technical aspects [11].…”
Section: Introductionmentioning
confidence: 99%
“…The nearer the value is to zero, the weaker the relationship. Many obstacles exist during the online transferring process, such as the limitation of social interaction and the lack of commitment, with a great deal of distraction [12]. Students in rural areas face technological accessibility, poor internet connectivity, and challenging study environments [2].…”
Section: Students' Attendance and Academic Performancementioning
confidence: 99%
“…Problems in internet access might hamper an effective online classroom experience [22]- [24]. A survey was conducted involving 322 Indonesian school students who participated in online learning during the Covid-19 pandemic and found that 55 percent of students were unsatisfied with the online learning mode [25].…”
Section: Problems In Internet Accessmentioning
confidence: 99%